1954
DOI: 10.1021/ja01640a030
|View full text |Cite
|
Sign up to set email alerts
|

Poison Ivy “Urushiol”

Abstract: Poison Ivy "Urushiol" 2959 of Via; m.p. 192.5-194°with previous softening. From the mother liquor by concentration and addition of water there was obtained an additional 161 mg., m.p. 189-192°, bubbles in melt, clear at 199°; 91% yield (two fractions).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

1955
1955
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 0 publications
0
27
0
2
Order By: Relevance
“…The chemical structure of urushiol and the mechanisms of its polymerization have already been clarified. [2][3][4] Urushiol, a mixture of 3-substituted pyrocatechol derivatives, is usually hardened with the laccasecatalyzed polymerization system. To date, few studies have focused on the viscoelastic properties of dried lacquer films.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structure of urushiol and the mechanisms of its polymerization have already been clarified. [2][3][4] Urushiol, a mixture of 3-substituted pyrocatechol derivatives, is usually hardened with the laccasecatalyzed polymerization system. To date, few studies have focused on the viscoelastic properties of dried lacquer films.…”
Section: Introductionmentioning
confidence: 99%
“…The saturated and the mono-, di-, and triene forms are present. Whereas urushiol derived from poison ivy is composed predominantly of compounds with C-15 side chains (5), poison oak urushiol contains more of the compounds with C-17 side chains (6,7). The di-and tri-olefins are the major components of both urushiols, and the two oils are highly cross reactive (8).…”
Section: Introductionmentioning
confidence: 99%
“…9,10) Our previous reported that the affinity of CTUDs (1)(2)(3)(4)(5)(6) to liposome membrane tended to increase with the increase of the carbon atomic length of the alkyl side chains. 14) In this study, we found that there was an apparent correlation between the antimicrobial activity and lipophilicity, although the activities observed varied slightly between the microorganisms tested.…”
Section: )mentioning
confidence: 99%